Особенности износа рабочей поверхности вращательного бурового инструмента - Бочковский, А.М. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
It is shown, that equipment of boring tools by inserts of the cylindrical form results in uneven equipment and uneven wear of a working part. The form of wear of a working surface repeats the form of a curve of factor of equipment.